Diagnostic Value of Diffusion-weighted Imaging and Apparent Diffusion Coefficient Values in the Differentiation of Breast Lesions, Histpathologic Subgroups and Correlation with Prognostic Factors using 3.0 Tesla MR - KAYA, HANDAN; UĞURLU, MUSTAFA ÜMİT (AVES, 2016)
Objective: The aim of this study was to evaluate the effect of the apparent diffusion coefficient (ADC) and diffusion-weighted imaging in differentiating benign from malignant breast lesions, histopathologic subtypes of breast tumors, and to find a correlation with prognostic factors using 3T MR. Materials and Methods: A total of 165 patients aged between 16 and 78 years with 181 histopathologically-verifed breast lesions were enrolled in this study. A 3T MR system and bilateral phased array breast coil was used. Diffusion-weighted imaging was performed with spin echo echo planar'' with b'' values: 50, 400, and 800 seconds/mm(2). ADC values were calculated for normal fibroglandular tissue and breast lesions. ADC values of independent groups were compared using Student's t-test. ROC analysis was used to find a threshold ADC value in the differentiation of lesions. Results: The mean ADC values were 1.35 +/- 0.16 x10(-3) mm(2)/s for normal fibroglandular tissue, 1.41 +/- 0.24 x10(-3) mm(2)/s for benign breast lesions and 0.83 +/- 0.19 x10(-3) mm(2)/s for malignant breast lesions. The AUC with ROC analysis was 0.945 and the threshold for ADC was 1.08 x10(-3) mm(2)/s with a sensitivity and specificity of 92% and 92%, respectively. The threshold value for ADC ratio was 0.9 with 96% sensitivity and 89% specificity. The mean ADC of malignant breast lesions was statistically lower for benign lesions (p<0.01). We found no correlation between the mean ADC values and ER-PR receptor, Her2, and Ki-67 values. Conclusion: Diffusion-weighted imaging has high diagnostic value with high sensitivity and specificity in differentiating malignant and benign breast lesions.
Keywords: Diffusion-weighted imaging; ADC; breast cancer; invasive ductal carcinoma; Ki-67; Her 2 expression; INVASIVE DUCTAL CARCINOMA; SIGNAL INTENSITY; CANCER; RECEPTOR